From Cash to Code: The Cultural Meaning of Financial Literacy among Women Traders in Makassar’s Traditional Markets - Amin, Andi Mustika (Malaqbi Publisher, 2025)
This qualitative phenomenological study explores how women traders in Makassar’s traditional markets experience and reinterpret financial literacy amid the cultural transition from cash-based to digital transactions. Drawing on in-depth interviews, participant observation, and focus group discussions across three major markets, the research conceptualizes financial literacy not merely as technical knowledge but as a relational and embodied practice rooted in trust, tactility, and moral economy. Findings reveal four major themes: (1) Tangibility and Embodiment of Value, where cash serves as sensory proof of labor and integrity; (2) Hybrid Trust Architectures, in which kinship and intergenerational mediation bridge confidence in digital systems; (3) Socially Situated Learning, where collective teaching through peer exchange sustains adaptive financial practices; and (4) Moral Reframing through Digital Visibility, where transaction records acquire new ethical significance as tools of proof and accountability. The study demonstrates that financial literacy evolves through communal learning, affective relationships, and moral negotiation, rather than through formal instruction alone. It argues that policies and fintech initiatives promoting financial inclusion must integrate cultural sensitivity, strengthen social mediators, and respect tactile economies to ensure sustainable adoption. Ultimately, the transition “from cash to code” represents not only a technological shift but a redefinition of value, trust, and moral responsibility in Makassar’s local markets.